Anesthetic Management of a Patient with ARC Syndrome - Arthrogryposis, Renal Dysfunction, and Cholestasis: A Case Report - Costa, Beatriz Figueiredo Mota Diniz; Oliveira, Maurício Vitor Machado; Senna, Maria Beatriz Assumpção Mourão Soares de; Delgado, Marina Ayres (Brazilian Journal of Case Reports, 2024)
ARC Syndrome, characterized by arthrogryposis, renal dysfunction, and cholestasis, is a rare genetic disorder often resulting in early mortality due to complications such as bleeding. This report details the anesthetic management of a 14-year-old male with type 1 ARC Syndrome, scheduled for gastrostomy and incisional hernioplasty due to severe malnutrition. The patient was presented with minor but relevant oral bleeding during surgery and, after receiving desmopressin, platelets transfusion and tranexamic acid, was able to be safely extubated. This case underscores the importance of thorough pre-anesthetic evaluation and tailored management strategies to address unique challenges presented by ARC Syndrome, particularly concerning coagulopathy and airway management. While existing literature on anesthetic approaches for ARC patients is limited, strategies such as desmopressin and tranexamic acid may offer benefits in managing bleeding tendencies, warranting further investigation into their effectiveness in this context.